Vytvoření modelu procesoru RISC-V - Nosterský, Milan (Vysoké učení technické v Brně. Fakulta informačních technologií, 2016)
Bakalářská práce se zabývá implementací modelu procesoru RISC-V v jazyce pro popis architektur CodAL. Teoretická část práce se zaměřuje na popis jazyka CodAL a klasifikaci procesorů. Praktická část práce se věnuje samotné implementaci procesoru RISC-V na úrovni instrukčního modelu a jeho testování. Dále se práce zabývá implementací MMU, časovačem a analýzou proxy kernelu.

This bachelor thesis deals with the implementations of RISC-V processor model in the language for architecture description  CodAL. The theoretical part of thesis is focused on the description of CodAL language and classification of processors. The practical part of thesis deals with the implementation of processor RISC-V on instruction accurate level and the model testing. The thesis also deals with the implementation of MMU, timer and analysis of the proxy kernel.
RISC-V Model Creation
Keywords: CodAL; Codasip; procesor; RISC-V; ADL; model; MMU; časovač; proxy kernel; CodAL; Codasip; processor; RISC-V; ADL; model; MMU; timer; proxy kernel